Pengembangan Lembar Kerja Peserta Didik pada Proses Pembelajaran Dasar Listrik dan Elektronika - Megawaty Gultom; Hambali Hambali (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2020)
This research is motivated by several things, namely the limitations of supporting books for student books, students still have difficulty mastering the learning material well in the subject matter of calculating electrical power and energy in the calculation concept and limitations of the LKPD which consists of a collection of questions only, the learning materials provided also very short and packaged in just one meeting. This study aims to develop LKPD in Basic Electrical and Electronics subjects in basic competencies 3.2 and 3.6 in class X TPTU which are valid and practical at SMKN 1 West Sumatra. This study is a Research and Development (R&D) research using the ADDIE model. This model consists of five stages, namely analysis, design, development, implementation, and evaluation. Data were collected using the LKPD validation and practicality instrument sheet, the LKPD validity questionnaire, and the LKPD practicality questionnaire. The subjects of this study were LKPD Basic Electricity and Electronics and the respondents in this study were students of class X TPTU B and teachers of DLE subjects at SMKN 1 West Sumatra. The results of this study obtained data on the average validity of LKPD from three validators in the valid category. The results of the practicality test by the teacher were stated in the very practical category and the practicality by students was stated in the very practical category. Thus LKPD Basic Electricity and Electronics are declared valid and practically used in learning the basic theory of electricity and electronics class X TPTU at SMK N 1 West Sumatra.